THE IMPORTANCE OF MIRZO ULUGBEK MADRASSAH IN DEVELOPING THE SYSTEM OF EDUCATION IN ITS TIME (Proceedings of International Educators Conference, 2024)
Enlightener scholar and statesman Abdurauf Fitrat wrote in his “Rahbari najot”: “Our country was famous as the source of enlightenment, rising of culture sun in its time”. Our state was well-known to the world thanks to thousands of popular scholars. Schools and madrassahs which educated hundreds of scientists were called as “cradle of world development” by Abdurauf Fitrat.